2023
DOI: 10.4103/aja2022115
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive semen examination in patients with pancreatic-sufficient and pancreatic-insufficient cystic fibrosis

Abstract: We examined a cohort of 93 cystic fibrosis (CF) male patients who were pancreatic-sufficient (PS-CF; n=40) or pancreatic-insufficient (PI-CF; n = 53). Complex semen examination was performed, including standard semen analysis, quantitative karyological analysis (QKA) of immature germ cells (IGCs), transmission electronic microscopy (TEM), biochemical analysis, and sperm DNA fragmentation by terminal deoxynucleotidyl transferase-mediated dUTP nickend labeling (TUNEL) assay. Azoospermia was diagnosed in 83 (89.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In our recent study of a cohort of adult Russian men diagnosed with CF, we found four patients who were compound heterozygotes for the L138ins variant (F508del/L138ins, n = 3; 2184insA/L138ins, n = 1) [7]. All patients developed pancreas sufficient CF (PS-CF) and obstructive azoospermia due to congenital bilateral aplasia of vas deferens.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our recent study of a cohort of adult Russian men diagnosed with CF, we found four patients who were compound heterozygotes for the L138ins variant (F508del/L138ins, n = 3; 2184insA/L138ins, n = 1) [7]. All patients developed pancreas sufficient CF (PS-CF) and obstructive azoospermia due to congenital bilateral aplasia of vas deferens.…”
Section: Discussionmentioning
confidence: 97%
“…Genes 2023, 14, 1407 2 of 10 Commonly, the frequency of CFTR gene variants has been found to be higher in infertile male patients compared to the general population, including Russian men with impaired fertility without diagnosed CF [5,6]. This is mainly due to Congenital Bilateral Aplasia of Vas Deferens (CBAVD, OMIM: 277180), which is characterized by obstructive azoospermia [2,7]. This excretory form of male infertility can be associated with CF or can be isolated (CBAVD syndrome) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%